To Peg or Not to Peg : A Template for Assessing the Nobler - Husain, Aasim (IMF Working Papers; Working Paper ;, 2006)
This paper proposes a template for assessing whether or not a country's economic and financial characteristics make it an appropriate candidate for a pegged exchange rate regime. The template employs quantifiable measures of attributes-trade orientation, financial integration, economic diversification, macroeconomic stabilization, credibility, and "fear-offloating" type effects-that have been identified in the literature as key potential determinants of regime choice. To illustrate, the template is applied to Kazakhstan and Pakistan. The results indicate a fairly strong case against a pegged regime in Pakistan. The implications for Kazakhstan are mixed, although changes in that economy in recent years strengthen the case against a peg.